1999
DOI: 10.1128/jcm.37.4.1217-1220.1999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Genotype of Hepatitis G Virus in Southeast Asia

Abstract: Hepatitis G virus (HGV) isolates obtained from 20 Myanmarese and 10 Vietnamese subjects were analyzed. A cluster of isolates not belonging to any known genotype of HGV was found in five Myanmarese subjects and three Vietnamese subjects by phylogenetic analysis, and we classified this new genotype as type 4. These results revealed that the HGV genome can be classified into at least four major genotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…DNA distance analyses showed that the South African isolates are distinct from any other group [Tucker et al, 1999]. Although the Vietnam/Myanmar isolates are more closely related to genotype 3 than any other, they appear sufficiently distinct for separate genotype grouping [Naito et al, 1999].…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…DNA distance analyses showed that the South African isolates are distinct from any other group [Tucker et al, 1999]. Although the Vietnam/Myanmar isolates are more closely related to genotype 3 than any other, they appear sufficiently distinct for separate genotype grouping [Naito et al, 1999].…”
mentioning
confidence: 84%
“…The GB virus-C and hepatitis G virus (hereinafter GBV-C/HGV) have been characterized as variants of a positive-strand, RNA flavivirus initially thought to be associated with hepatitis [Simons et al, 1995;Yoshiba et al, 1995;Linnen et al, 1996;Heringlake et al, 1996]. This serves as a clarification note and proposal subsequent to recent papers [Naito et al, 1999;Tucker et al, 1999], containing conflicting nomenclature for GBV-C/HGV genotypes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…GBV-C is classified into six major genotypes, type 1-6 [Muerhoff et al, 1996[Muerhoff et al, , 2006Tucker and Smuts, 2001;Van der Bij et al, 2005]. The genotypes tend to follow a geographical distribution patterns: type 1 predominates in West Africa, type 2 in Europe and the United States, type 3 in parts of Asia, type 4 in Southeast Asia, and type 5 in South Africa [Fukushi et al, 1996;Mukaide et al, 1997;Naito et al, 1999;Tucker and Smuts, 2001;Hattori et al, 2003]. One study identified a novel group of GBV-C sequences among individuals living in Indonesia [Handajani et al, 2000].…”
Section: Introductionmentioning
confidence: 99%